MENINGKATKAN PENDIDIKAN & PELATIHAN KOMPETENSI GURU PRODUKTIF DAN SISWA-SISWI DENGAN KAMAJUAN TEKNOLOGI 4.0 BERBASIS IOT DI SMKN 1 PARITTIGA BANGKA BARAT - Yudhi, Yudhi; Dwisaputra, Indra; Ocsirendi, Ocsirendi; Saputra, Gilang; Hera, Hera (Jurnal Pengabdian Masyarakat Polmanbabel, 2025)
In improving the quality of education that leads to vocational programs, the Bangkabelitung Manufacturing Polytechnic is one of the institutions with almost 80% of study programs in the vocational direction. Where in general vocational programs lead to values ??that are guided by the skills they rely on. With an educational background, all lecturers at the Bangkabelitung State Manufacturing Polytechnic have vocational-based education. The increase in study programs in the electronics department will certainly add color to the scientific aspect specifically regarding Information Technology, especially on the Internet of Things (IoT), with the existence of community service programs which is one of the tri dharma of higher education, as well as efforts to increase the competence of teachers and students, especially in vocational schools or schools that are oriented towards vocational programs. Therefore we provide training to teachers and students on understanding technology 4.0 which includes an understanding of IoT. By using simulation tools in the form of sensors, microcontrollers, WiFi devices, and output using DC/AC motors as loads. It is hoped that 90% of teachers and students understand technology 4.0 based on the Internet of Things.